Penerapan Aromaterapi Lemon untuk Mengatasi Nyeri pada Pasien Post Laparatomi e.c Hernia Umbilikal di Ruang Bedah RSUP Dr. M. Djamil Padang - Setyawan, Muhammad Rizki (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2024)
Laparotomy is an open surgical procedure that requires a sufficiently large incision to access the abdominal cavity and it’s organs for diagnosis, repair, or removal of diseased or injured organs. Based on disease data from the women's surgical ward in April 2024, there were 5 patients undergoing laparotomy, as laparotomy remains a common open abdominal surgery today. This final paper aims to provide information on the application of lemon aromatherapy to reduce pain intensity in post-laparotomy e.c umbilical hernia patients in the surgical ward of RSUP Dr. M. Djamil Padang. The study design used a case report, with the population consisting of all post laparotomy patients in April, totaling 5 individuals. The sample included 2 clients with specific characteristics based on inclusion and exclusion criteria, and pain assessment was conducted using the Numerical Rating Scale (NRS). The evaluation results showed that the intervention of lemon aromatherapy for Ms. M and Ms. L in reducing post-laparotomy pain demonstrated a change in pain scale before and after therapy. For both clients, there was a reduction in pain scale: Ms.M’s pain decreased from 6 to 2, and Ms. L’s pain decreased from 5 to 1. The recommendation of this study is that lemon aromatherapy should be considered as one of the interventions that nurses can use to reduce post laparotomy pain intensity. Keywords: Aromatherapy, Lemon Essential, Pain, Laparotomy Surgery